Human creativity during COVID-19 pandemic: the project Pandemic Objects as an example of sociological reflections on design - Rojek-Adamek, Paulina (Creativity Studies, 2023)
This article proposes to look at how the COVID-19 pandemic has affected the valuation of the world of material culture, and how the subject itself can become an inspiration to describe this particular time. Naive anthropomorphism, and thus criticism of the view of the superior role of human, although present for many years, has taken on a new meaning at this particular time. As a theoretical framework for presenting the proposed issues, I adopt the reference to the interpretation of the concept of an “object” present in the social sciences and humanities, as well as the role of designers and the explication of design in the literature. The picture will be complemented by a reference to the Pandemic Objects project, implemented in 2020 by the Victoria and Albert Museum in London, United Kingdom.